2011
DOI: 10.1016/j.jpeds.2010.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Maintenance of Neural Tube Defects Prevention in a High Prevalence State

Abstract: Objective To assess the efficacy of folic acid (FA) supplementation and fortification in preventing neural tube defects (NTDs) in a high prevalence region of the US. Study design Active and passive surveillance methods were used to identify all fetuses/infants affected by an NTD in South Carolina. Prevalence rates were compared with FA intake to determine the effects of increased intake on NTD occurrence and recurrence. Results From 1992–2009, 916 NTD cases occurred in South Carolina with isolated defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…The smallest decrease occurred in the state of California in the USA (15?5 %) (23) . Twenty-one articles reported on the prevalence of spina bifida before and after flour fortification (15,16,19,(21)(22)(23)25,26,28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) . The largest reductions reported were in Costa Rica (61 %) (28) , Canada (55 %) (21) and Chile (55 %) (25) The latter study examined the number of NTD cases between the years 1998 and 2007.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The smallest decrease occurred in the state of California in the USA (15?5 %) (23) . Twenty-one articles reported on the prevalence of spina bifida before and after flour fortification (15,16,19,(21)(22)(23)25,26,28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) . The largest reductions reported were in Costa Rica (61 %) (28) , Canada (55 %) (21) and Chile (55 %) (25) The latter study examined the number of NTD cases between the years 1998 and 2007.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that the decrease in the number of spina bifida cases is greater than the decrease in anencephaly cases (15,21,30,32,36,37) ; however, other studies have shown a greater reduction in the latter (16,23,26,35,39,40) .…”
Section: References Identified Medline Viamentioning
confidence: 98%
“…It has been shown to be an effective means of lowering recurrence risks for future pregnancies. 12,18,19 But this supplementation was not effective in our patient because anencephaly had recurred in the second child, associated with a rachischisis. Depending on the sex of the affected fetus, Lalouel JM and al evaluated that the risk of recurrence of NTDs is multiplied by 0.051 after one female affected, by 0.058 after one male affected.…”
Section: Discussionmentioning
confidence: 82%
“…One case of NTDs recurrence in group without prevention was similar with our case report, the first child had a spina bifida and the second a craniorachischisis. 19 Concerning the diagnostic means, craniorachischisis can be detected on ultrasound at gestational age of 13 weeks and magnetic resonance imaging at 22 weeks. 2,11 In our case, the rachischisis was diagnosed at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have since examined whether fortification led to a reduction in NTD prevalence in the population as a before-versus-afterintervention-phenomenon. Most studies have indeed observed a reduction associated with the timing of fortification (Honein et al, 2001;Feldkamp et al, 2002;Williams et al, 2002;Canfield et al, 2005;Williams et al, 2005;Boulet et al, 2008;L opez-Camelo et al, 2010;Collins et al, 2011).…”
Section: Introductionmentioning
confidence: 99%